The Narrative Component from a Cultural Perspective Youcef Idris’s Al-Haram — A Case Study - Ikram, Mekhfi (Journal of Ecohumanism, 2026)
The Marxist materialist vision insists that literature is a mirror of society, and that the task of literature is to enlighten and transform social perceptions; otherwise, it is merely an intellectual luxury. Hence, realism came to dominate narrative creativity, surpassing the mythological reveries that had characterized classical literature. This approach seeks to trace social issues through one of the most important novels by Youcef Idris. Accordingly, the study adopts two trajectories: A theoretical trajectory, through which it addresses the creative biography of the writer Youcef Idris and sheds light on the cultural approach as a serious contemporary critical stake. And an applied trajectory, through which it attempts to examine the social issues embedded in the novel.